2013
DOI: 10.3791/50376
|View full text |Cite
|
Sign up to set email alerts
|

Atom Probe Tomography Studies on the Cu(In,Ga)Se<sub>2</sub> Grain Boundaries

Abstract: Compared with the existent techniques, atom probe tomography is a unique technique able to chemically characterize the internal interfaces at the nanoscale and in three dimensions. Indeed, APT possesses high sensitivity (in the order of ppm) and high spatial resolution (sub nm).Considerable efforts were done here to prepare an APT tip which contains the desired grain boundary with a known structure. Indeed, sitespecific sample preparation using combined focused-ion-beam, electron backscatter diffraction, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…In the grains, a Na concentration of 30-60 ppm was found [38]- [41], whereas K could not be detected, as it was below the detection limit of 60 ppm/amu [38] and 45 ppm/amu [40]. Hence, it seems to be hard to detect K in the grains by APT and the Na content in the grains can be better detected by APT as its detection limit is lower (about 5-10 ppm/amu).…”
Section: Potassium In Cigs Solar Cellsmentioning
confidence: 91%
“…In the grains, a Na concentration of 30-60 ppm was found [38]- [41], whereas K could not be detected, as it was below the detection limit of 60 ppm/amu [38] and 45 ppm/amu [40]. Hence, it seems to be hard to detect K in the grains by APT and the Na content in the grains can be better detected by APT as its detection limit is lower (about 5-10 ppm/amu).…”
Section: Potassium In Cigs Solar Cellsmentioning
confidence: 91%
“…The outer rim of the grid is kept longer than the tips for sample protection during grid manipulation. Detailed information on this preparation procedure is also available as a video [8].…”
Section: Methodsmentioning
confidence: 99%
“…Examples are numerous and include local phase transformations triggered by segregation [31]; the investigation of precipitation [15] and partitioning phenomena [35]; the characterization of the formation of oxide layers [5] and radiation-induced microstructural changes [26]; the prove that there is no segregation at a lattice defect above the detection limit of APT [25]; the investigation of correlations between segregation and dislocations [6], stacking faults [7], or for understanding the correlation between solute segregation and the character of grain boundaries [14,20,36,4,8]. Atom probe tomography (APT), having the capacity to measure three-dimensional (3D) chemistry with equal detection sensitivity (of a few ppm) for all elements at near atomic spatial resolution [16], can provide answers to some of these questions.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments, however, observed that the hole concentration throughout the CIGS layers is also increased after Na doping. Choi et al, [18] Couzinie-Devy et al, [25,33] Laemmle et al, [32] and Cojocaru-Mirédin et al [34] found that the concentration of Na in the CIGS grain interiors is around 13-150 ppm (around 10 17 -10 18 cm −3 ), which is high enough to alter the electrical properties significantly. Moreover, recent atom probe tomography studies provide clear evidence for the presence of Na inside the CIGS grains.…”
Section: Doi: 101002/aenm201601191mentioning
confidence: 99%
“…Considering that the diffusion barrier of Na in CIGS was measured and calculated to be around 0.31-0.51 eV, [32,38,45,49] only part of the Na can diffuse out and some of Cu can also diffuse back from the surfaces and grain boundaries into the grains, so the resultant increase of the V Cu and hole concentration should be much lower than 10 18 cm −3 . Choi et al, [18] Couzinie-Devy et al, [25,33] Laemmle et al, [32] and Cojocaru-Mirédin et al [34] found that the concentration of Na in the CIGS grain interiors is around 13-150 ppm (around 10 17 -10 18 cm −3 ), which can be explained according to the leftover of Na Cu . [8,23] Since the resultant increase of the V Cu and hole concentration is only 10 16 cm −3 , much lower than the ideal value (10 18 − 10 13 ≈10 18 cm −3 ), there should be a high concentration of Cu diffusing back or leftover of Na Cu in the grains with a concentration on the order of 10 18 −10 16 ≈10 18 cm −3 .…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%